Paclitaxel and trastuzumab treatment affects insulin growth factor I expression in breast cancer cell lines (Bangladesh Journal of Pharmacology, 2015)
Breast cancer is the most common type of cancers and second primary cause of death among women. Insulin-like growth factor I (IGF-1) signaling pathway plays a vital role in cancer cell survival, proliferation, chemotaxis and angiogenesis. In this study, the effect of combination of two drugs, paclitaxel and trastuzumab on IGF signaling and cell cycle arrest in breast cancer cell lines, T47D and Hs0578T were explored. The interaction of paclitaxel and trastuzumab on IGF-1 signaling pathway was studied with IGF-1 and phosphoinositide 3-kinase inhibitor, LY294002. The protein expression of IGF signaling molecules were reduced in the drug treated cancer cells. LY294002 and IGF-1 with paclitaxel and trastuzumab treatment inhibited phosphorylated Akt. During G0/G1 phase, cell cycle arrest and accumulation of apoptotic cells were observed in drug treated cancer cells. The synergistic effect of paclitaxel and trastuzumab decreased the multiplication of breast cancer cells by altering the expression of IGF-I signaling molecules. This combination proves to be one of the useful methods to treat breast cancer.